Chapter 47 Latin America - Mandolessi, Silvana (Taylor & Francis, 2023)
Chapter 47: This chapter examines memory activism in Latin America, focusing on memory struggles on the cycle of political violence during the second half of the 20th century. First, the article describes the main features that characterize memory activism in the region: first, Latin American memory activism is rooted in the human rights movement that emerged during the 70s and consolidated in the following decades; second, the importance of truth commissions; third, the circulation of actors, memory practices and repertoires of actions across the continent, and, finally, the different outcome of memory activism in the different Latin American countries. After assessing this first wave of mobilizations, the article addresses the second wave of memory activism that emerged at the beginning of the twenty-first century, marked by the rise of new kinds of violence, carried out by state and non-state actors, with different degrees of collusion. On the one hand, this second wave adds new layers of complexity to the understanding of the past by incorporating elements of ethnicity, class and gender, which had previously only played a secondary role. On the other hand, it links both periods, by showing the continuities between past and present-day violence.